Myositis-specific autoantibodies and their association with malignancy in Italian patients with polymyositis and dermatomyositis. Issue 2 (February 2017) - Ceribelli, Angela; Isailovic, Natasa; De Santis, Maria; Generali, Elena; Fredi, Micaela; Cavazzana, Ilaria; Franceschini, Franco; Cantarini, Luca; Satoh, Minoru; Selmi, Carlo
Abstract This study aims to characterize myositis-specific antibodies in a well-defined cohort of patients with idiopathic inflammatory myopathy and to determine their association with cancer. Sera from 40 patients with polymyositis, dermatomyositis, and controls were tested by protein and RNA immunoprecipitation to detect autoantibodies, and immunoprecipitation-Western blot was used for anti-MJ/NXP-2, anti-MDA5, and anti-TIF1γ/α identification. Medical records were re-evaluated with specific focus on cancer. Anti-MJ/NXP-2 and anti-TIF1γ/α were the most common antibodies in dermatomyositis. In six dermatomyositis cases, we found five solid forms of cancer and one Hodgkin's lymphoma in long-term remission. Among patients with cancer-associated dermatomyositis, three were positive for anti-TIF1γ/α, two for anti-Mi-2, and one for anti-MJ/NXP-2. The strongest positivity of anti-TIF1γ was seen in two active forms of cancer, and this antibody was either negative or positive at low titers in the absence of cancer or in the 7-year remission Hodgkin's lymphoma. Four out of twenty (20 %) patients with polymyositis had solid cancer, but no specific association with autoantibodies was identified; further, none of the four cases of antisynthetase syndrome had a history of cancer. No serum myositis-associated autoantibody was observed in control sera, resulting in positive predictive value 75 %, negative predictive value 78.5 %, sensitivity 50 %, specificity 92 %, and area under the ROC curve 0.7083 for the risk of paraneoplastic DM in anti-TIF1γ/α (+) patients. Myositis-specific autoantibodies can be identified thanks to the use of immunoprecipitation, and their association with cancer is particularly clear for anti-TIF1γ/α in dermatomyositis. This association should be evaluated in a prospective study by immunoprecipitation in clinical practice.